Nasal cytology: Methodology with application to clinical practice and research. Issue 9 (9th July 2018) - Heffler, E.; Landi, M.; Caruso, C.; Fichera, S.; Gani, F.; Guida, G.; Liuzzo, M. T.; Pistorio, M. P.; Pizzimenti, S.; Riccio, A. M.; Seccia, V.; Ferrando, M.; et al.
Summary: Nasal cytology is an easy, cheap, non‐invasive and point‐of‐care method to assess nasal inflammation and disease‐specific cellular features. By means of nasal cytology, it is possible to distinguish between different inflammatory patterns that are typically associated with specific diseases (ie, allergic and non‐allergic rhinitis). Its use is particularly relevant when other clinical information, such as signs, symptoms, time‐course and allergic sensitizations, is not enough to recognize which of the different rhinitis phenotypes is involved; for example, it is only by means of nasal cytology that it is possible to distinguish, among the non‐allergic rhinitis, those characterized by eosinophilic (NARES), mast cellular (NARMA), mixed eosinophilic‐mast cellular (NARESMA) or neutrophilic (NARNE) inflammation. Despite its clinical usefulness, cheapness, non‐invasiveness and easiness, nasal cytology is still underused and this is at least partially due to the fact that, as far as now, there is not a consensus or an official recommendation on its methodological issues. We here review the scientific literature about nasal cytology, giving recommendations on how to perform and interpret nasal cytology.